Patriarchal Legitimization Strategies in Igbo Gender-Related Taboos: A Case for Critical Discourse Analysis - Ezeifeka, Chinwe RoseAnn (Advances in Social Sciences Research Journal, 2019)
This paper investigates gender-related Igbo taboos and their subtle recruitment in legitimising and sustaining patriarchy in Igbo culture. Thirty-eight taboos in the domains of inheritance, economic activities, family, leadership, marriage and widowhood were collected through participant observation and interviews. Applying ethnomethodological indexicality and reflexivity and Critical Discourse Analysis (CDA), strategies like dominant hegemonic masculinity and femininity, naturalisation, silencing, proximisation, positive-self and negative-other presentation are identified as constructing men’s superiority and women subordination. The paper calls for their deconstruction and delegitimisation for maximum harnessing of optimum human potentials in view of the global benchmark for gender equality by 2030.